A Study on Factors Affecting Mobile Phone Buying Behaviour in Bhubaneswar and Cuttack - Agarwal, Varun; Sahoo, Rashmita; Agarwal, Ankita (Indian Journal of Marketing, 2019)
Over the past few years, people's obsession with regard to mobile phones has been on the rise. This research threw light on the factors affecting consumer behaviour of mobile phone buyers in Bhubaneswar and Cuttack, popularly known as the twin cities of Odisha. The study depicted in detail the reasons behind people's desire to purchase a mobile phone, the factors influencing people while making the purchase, and the factors that motivated them to make the final purchase decision. From an extensive study of the existing literature available, it was found that the factors that instigate buying behaviour have really shown a great deal of dynamism since the last decade. The fast-changing technology of mobile telephony has truly become the driver of this unsteadiness. Most of the existing studies have focused on factors like price, features, brand, service, brand loyalty, and operating system with respect to mobile phones. Yet, it is believed that the impact of such factors keeps changing from time to time. Hence, it was deemed justifiable to conduct an updated study on these factors and also consider any other mediating factors in order to help the industry as well as academicians to understand consumers better and design products accordingly. The data for the research were collected using a structured questionnaire with a sample size of 610 respondents belonging to the twin cities of Odisha. Data were analyzed using descriptive statistics as well as regression analysis. From the findings of the study, it was inferred that in each price category, the companies dealing with mobile phones should focus on features and technology.